2011
DOI: 10.1146/annurev-neuro-061010-113717
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Inhibition within the Telencephalon: “Where the Wild Things Are”

Abstract: In this review, we first provide a historical perspective of inhibitory signaling from the discovery of inhibition through to our present understanding of the diversity and mechanisms by which GABAergic interneuron populations function in different parts of the telencephalon. This is followed by a summary of the mechanisms of inhibition in the CNS. With this as a starting point, we provide an overview describing the variations in the subtypes and origins of inhibitory interneurons within the pallial and subpal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
236
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(241 citation statements)
references
References 223 publications
(292 reference statements)
5
236
0
Order By: Relevance
“…Previously, VIPϩ cell loss of function experiments have been performed with either photolytic lesions of a small subset of VIPϩ cells (Fu et al 2014) or tetanus toxin-mediated lesions (Fu et al 2015). It was shown that the gain in the visual response during locomotion (Niell and Stryker 2010) was abolished by lesion of VIPϩ cells.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, VIPϩ cell loss of function experiments have been performed with either photolytic lesions of a small subset of VIPϩ cells (Fu et al 2014) or tetanus toxin-mediated lesions (Fu et al 2015). It was shown that the gain in the visual response during locomotion (Niell and Stryker 2010) was abolished by lesion of VIPϩ cells.…”
Section: Discussionmentioning
confidence: 99%
“…During visual stimulation, the thalamocortical circuit likely engages VIPϩ cells through a monosynaptic (Fu et al 2015) or polysynaptic excitatory circuit from the thalamus. However, during spontaneous activity or locomotion, top-down (Zhang et al 2014) or cholinergic inputs (Alitto and Dan 2012;Eckenstein et al 1988;Letzkus et al 2011) may be responsible for depolarizing these cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[2]). The GABAsynthesizing enzyme glutamic acid decarboxylase (GAD) is expressed by all GABAergic interneurons, and the calcium binding proteins calbindin (CB), calretinin (CR), or parvalbumin (PV) [2] are expressed individually or in combination with the neuropeptides somatostatin (SST), neuropeptide Y (NPY), cholecystokinin, and vasoactive intestinal peptide (VIP) [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…However, sequential activity may also emerge by local mechanisms, patterned by the different biophysical properties of CA1 pyramidal cells and their interactions with local interneurons, which discharge at different times during a ripple (28)(29)(30). A putative function of the rich variety of interneurons is temporal organization of principal cell spiking (29)(30)(31)(32). We tested the "localcircuit" hypothesis by comparing the probability of participation and sequential firing of CA1 neurons during theta oscillations, natural spontaneous ripple events, and "synthetic" ripples induced by local optogenetic activation of pyramidal neurons.…”
mentioning
confidence: 99%